2022
DOI: 10.7759/cureus.25055
|View full text |Cite
|
Sign up to set email alerts
|

Vermiform Appendix and the Potential for Missed Pathologies

Abstract: Introduction The appendix is considered an appendage of little value and is often treated disdainfully, be it as part of evolutionary process, on a grossing table, under a microscope or while archiving specimens and slides. It is only recently, with data indicating its importance in gut immunity and as the origin of pseudomyxoma, that its space in a human body appears vindicated. Aim Our aim was to screen the histopathologic spectrum of appendix lesions observed in our hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The process begins at the appendiceal tip and will proceed proximally over time and may affect the entire appendix. No treatment is required, however, as this is usually found incidentally, the prognosis is related to the underlying condition that led to resection [18][19][20][21][22][23].…”
Section: Fibrous Obliterationmentioning
confidence: 99%
“…The process begins at the appendiceal tip and will proceed proximally over time and may affect the entire appendix. No treatment is required, however, as this is usually found incidentally, the prognosis is related to the underlying condition that led to resection [18][19][20][21][22][23].…”
Section: Fibrous Obliterationmentioning
confidence: 99%
“…Several rare conditions linked to the vermiform appendix have been reported in the literature without fitting into any of the three main categories presented above. A retrospective cross-sectional study revealed that some appendectomy specimens were infested with Enterobius vermicularis, i.e., pinworm infection [165]. Other parasites reportedly found in the vermiform appendix include Taenia spp.…”
Section: Other Diagnoses Associated With the Vermiform Appendixmentioning
confidence: 99%
“…Other parasites reportedly found in the vermiform appendix include Taenia spp. (tapeworm), Hymenolepis nana (dwarf tapeworm), Ascaris lumbricoides (roundworm), Trichuris trichiura (whipworm), Schistosoma haematobium, Schistosoma mansoni, Giardia lamblia, and the protozoan Entamoeba histolytica [165,166]. Such parasite infections may further cause appendicular colic [167] or appendicitis [167][168][169].…”
Section: Other Diagnoses Associated With the Vermiform Appendixmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been other calls for a more thorough examination of the appendix following routine appendectomy. For example, a recent retrospective cross-sectional study showed that a significant portion of rare appendiceal pathologies were not suspected either radiologically or clinically prior to microscopic analysis [11]. Moreover, given the dearth of research with respect to the treatment of patients with appendiceal goblet cell adenocarcinoma, it is important to identify cases of this rare tumor and add to the literature.…”
Section: Yablonski Et Al 26mentioning
confidence: 99%